Passive recovery strategies after exercise: A narrative literature review of the current evidence - Cullen, M.-F.; Casazza, G.; Davis, B. A. (Current Sports Medicine Reports, 2021)
Passive recovery techniques are popular and offer a diverse spectrum of options for athletes and the clinicians providing care for them. These techniques are intended to minimize the negative effects of training or competition, thus enabling the athlete a quicker return to peak performance. Current evidence demonstrates improved athlete recovery with compression garments, cold water immersion, partial body cryotherapy, hyperbaric oxygen, and vibratory therapies. Other popular modalities, such as compression devices, whole body cryotherapy, percussive gun-assisted therapy, neuromuscular electrical stimulation, and pulsed electromagnetic therapy lack convincing evidence concerning athlete recovery. This article seeks to review the current literature and offer the reader an updated understanding of the mechanisms for each modality and the evidence regarding each modality's potential benefit in an athlete's recovery strategy.